2007
DOI: 10.1111/j.1540-4781.2007.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Requests and Apologies in Spanish and French: Impact of Study Abroad and Strategy‐Building Intervention

Abstract: The primary aim of this study was to assess the impact of a curricular intervention on studyabroad students' use of language-and culture-learning strategies and on their acquisition of requests and apologies. The intervention consisted of a brief face-to-face orientation to learning speech acts, a self-study guidebook on language and culture strategies, which included strategies for learning speech acts, and electronic journaling by the students. The study used an experimental design in which the participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(107 citation statements)
references
References 30 publications
12
93
0
2
Order By: Relevance
“…The current literature has focused on researching the speech act of apology in different cultural contexts as well as non-native speakers' pragmatic competence of making apologies in a target language (Al-Zumor, 2011;Bataineh & Bataineh, 2008;Bergman & Kasper, 1993;Cheng, 2011;Cohen & Shively, 2007;Garcı´a, 1989;House, 1988;Linnell, 1992;Kondo, 1997;Olshtain, 1983;Sabate & Curell, 2007;Shardakova, 2005;Sugimoto, 1997;Trosborg, 1987;Xiang, 2004). However, there have been few studies on responses to apologies, and differences in apology responses by speakers from different cultures have been overlooked as well.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature has focused on researching the speech act of apology in different cultural contexts as well as non-native speakers' pragmatic competence of making apologies in a target language (Al-Zumor, 2011;Bataineh & Bataineh, 2008;Bergman & Kasper, 1993;Cheng, 2011;Cohen & Shively, 2007;Garcı´a, 1989;House, 1988;Linnell, 1992;Kondo, 1997;Olshtain, 1983;Sabate & Curell, 2007;Shardakova, 2005;Sugimoto, 1997;Trosborg, 1987;Xiang, 2004). However, there have been few studies on responses to apologies, and differences in apology responses by speakers from different cultures have been overlooked as well.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some ethnographic studies (e.g., Siegal, 1995) did not meet this criterion because they did not code the data for pragmalinguistic analysis. Neither did this study present the changes of certain pragmatic features over the 18 months 6 Some longitudinal studies such as Cohen and Shively (2007) and Shively (2011) did not meet this criterion because their design involved instruction or training. For example, 7.…”
Section: Methodsmentioning
confidence: 99%
“…As more and more students and institutions of higher education become interested in SA, an array of research has been done on SA. Most research has shown SA programs to be facilitative in acquiring the second language skills (i.e., listening, reading, speaking and writing) (Cai, Li, & Liu, 2013;Chen, 2007;Hernández, 2010;Lafford, 2004;Lindseth, 2010;Pérez-Vidal & Juan-Garau, 2011;Taguchi, 2008;Taillefer, 2005) as well as intercultural competence (Batalle, 2010;Cohen & Shively, 2007;Jackson, 2011;Martinsen, 2011;Xu, Case, & Wang, 2009). It has been claimed that students abroad become significantly more fluent (Lafford, 2004;Segalowitz & Freed, 2004) and significantly increase their vocabulary after their experience in the foreign country (Dewey, 2008;Llanes & Muñoz, 2009;Milton & Meara, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%